2016
DOI: 10.1038/emm.2016.81
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and function of AMPK in physiology and diseases

Abstract: 5′-adenosine monophosphate (AMP)-activated protein kinase (AMPK) is an evolutionarily conserved serine/threonine kinase that was originally identified as the key player in maintaining cellular energy homeostasis. Intensive research over the last decade has identified diverse molecular mechanisms and physiological conditions that regulate the AMPK activity. AMPK regulates diverse metabolic and physiological processes and is dysregulated in major chronic diseases, such as obesity, inflammation, diabetes and canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
771
1
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 880 publications
(806 citation statements)
references
References 148 publications
(158 reference statements)
19
771
1
15
Order By: Relevance
“…LKB1, calmodulin‐dependent protein kinase kinase β (CaMKKβ), and transforming growth factor β‐activated kinase (TAK1) are upstream kinases that can activate AMPK by phosphorylating Thr172, which is situated in the activation loop of the α‐subunit (Jeon, 2016). In our study, we found that LPS stimulation inhibits LKB1 phosphorylation, but it does not affect CaMKKβ and TAK1 phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…LKB1, calmodulin‐dependent protein kinase kinase β (CaMKKβ), and transforming growth factor β‐activated kinase (TAK1) are upstream kinases that can activate AMPK by phosphorylating Thr172, which is situated in the activation loop of the α‐subunit (Jeon, 2016). In our study, we found that LPS stimulation inhibits LKB1 phosphorylation, but it does not affect CaMKKβ and TAK1 phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it has been demonstrated that activation of AMPK is responsible for inducing apoptosis via the mitochondrial pathway (12,13). However, AMPK is also known to play a protective role in cancer cells under metabolic stressed conditions by maintenance of energy homeostasis and modulation of autophagy, making the influence of AMPK on cancer progression controversial (14,15).…”
Section: Resultsmentioning
confidence: 99%
“…This compound, that mimics the intracellular increase in AMP, is capable of phosphorylating AMPK promoting glucose uptake and lipid oxidation in skeletal muscle 26 . Animal experiments also suggest that AMPK activation in skeletal muscle is capable of enhancing lipid oxidation and the glycogen resynthesis rate in response to exercise (having a protective effect on muscle glycogen stores) through the muscle contraction stimulus per se and through the increase of calcium release 27 . Continuous and repetitive muscle contraction that is characteristic of exercise acts as a stressor agent.…”
Section: Physical Exercise and Glucose Uptake Mediated By Ampkmentioning
confidence: 99%